Reminiscence of H. R. Voth - Voth, H. R. (Henry R.), 1855-1931.
Transcript of Voth's reminiscence of his 1874 voyage from Hamburg, Germany, to New York, N.Y., with other Russian Mennonite emigrants.
Typewritten transcript.
Mennonite clergyman.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Mennonites, Russian -- United States; Germany -- Emigration and immigration; Hamburg (Germany) -- Emigration and immigration; New York (N.Y.) -- Emigration and immigration; Russia -- Emigration and immigration; United States -- Emigration and immigration; Clergy